White gourd leaf extract corrosion inhibitor, preparation method and application
Through the corrosion inhibitor combined with winter melon leaf extract and iodide, an adsorption film is formed on the copper surface, solving the problems of poor solubility and environmental pollution of existing corrosion inhibitors, achieving efficient and environmentally friendly corrosion inhibition on metal copper surfaces, and improving the corrosion resistance of metallic copper surfaces Corrosion inhibitory performance and resource utilization rate.
Patent Information
- Application Number
- CN202410736194.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-01-03
AI Technical Summary
During the use of existing corrosion inhibitors, there are problems such as poor solubility, low corrosion inhibition performance, complex synthesis route, high cost and serious environmental pollution. It is difficult to effectively protect metal copper materials, resulting in shortening of the service life of industrial equipment and safety hazards.
Winter melon leaf extract is used as the corrosion inhibitor, and extracts containing specific chemical components are obtained through an autoclave and combined with iodide to form an adsorption film to block the corrosion medium on the copper surface, improving corrosion inhibition performance.
It achieves efficient and environmentally friendly corrosion inhibition of metal copper surface, reduces the damage of pickling solution to metal substrates, improves the solubility of corrosion inhibitors and material resource utilization, and meets the needs of large-scale applications.
Smart Images

Figure CN119243164A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of corrosion inhibitors, and in particular to a wax gourd leaf extract corrosion inhibitor, a preparation method and an application thereof. Background Art
[0002] The metal material copper is widely used in various industries related to the national economy and people's livelihood, such as machinery manufacturing, marine industry, national defense industry, construction industry, transportation industry, etc., and it plays a very important role. However, metal materials are very susceptible to corrosion from corrosive media (such as acids, alkalis, salts, etc.) in the environment during use. The corrosion of metals is closely related to the safety of mechanical devices, instruments and equipment, production buildings, work platforms, metal pipes, etc. prepared on the basis of metals. Corrosion has greatly shortened the service life of many industrial equipment, which not only brings huge economic losses and serious environmental pollution, but also may cause serious safety accidents. With the continuous acceleration of my country's industrialization process and the continuous advancement of the deep concept of green chemistry, it is urgent to find a green and pollution-free anti-corrosion road.
[0003] At present, there are many types of applications for copper corrosion inhibitors, but most of them have many problems during use. For example, the corrosion inhibitor has poor solubility, low corrosion inhibition performance, complex synthesis route, high cost and pollution to the ecological environment. Therefore, it is particularly important to develop new environmentally friendly, widely available and cost-effective corrosion inhibitors. Summary of the invention
[0004] The purpose of the present invention is to provide a wax gourd leaf extract corrosion inhibitor, a preparation method and an application thereof, so as to achieve the technical effects of wide material sources, high cost performance, good corrosion inhibition performance, and pure natural and pollution-free ingredients.
[0005] A wax gourd leaf extract corrosion inhibitor comprises the following components: 2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-4H-chromene-4-one, 7-hydroxy-3-[4-hydroxy-3-(3-methyl-2-butyl)phenyl]benzopyran-4-one, p-hydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid and pyridine-3-carboxylic acid.
[0006] A method for preparing a wax gourd leaf extract corrosion inhibitor comprises the following steps:
[0007] S1: Wash the wax gourd leaves with water and dry them naturally;
[0008] S2: Grinding the dried wax gourd leaves into wax gourd leaf powder;
[0009] S3: Weigh a certain amount of wax gourd leaf powder and a certain amount of water, stir them evenly, and then dispense them into a polytetrafluoroethylene beaker, and then place the stirred liquid in an autoclave for extraction. After the extraction reaction, filter to obtain a filtrate, and freeze the obtained filtrate;
[0010] S4: placing the frozen filtrate into a freeze drying box for freeze drying to obtain the wax gourd leaf extract corrosion inhibitor.
[0011] In order to better implement the present invention, further, in step S3, the pressure in the autoclave is 4-6Mpa.
[0012] In order to better realize the present invention, further, in the high-pressure extraction reaction process of step S3, nitrogen needs to be flushed into the autoclave. In the reaction, in order to prevent the extract from being oxidized, nitrogen is flushed into the reactor, which can effectively prevent the extract from contacting with oxidizing substances such as oxygen, thereby achieving the purpose of protecting the extract and further ensuring the effective substances of the extract. In addition to nitrogen, other inert gases are all acceptable.
[0013] In order to better realize the present invention, further, in the step S3, the extraction time in the autoclave is 1-3h. The present invention adopts an autoclave for extraction, and the main reason is that high-pressure extraction can effectively reduce solvent consumption, shorten the extraction time, and thus improve the extraction efficiency. During the high-pressure extraction process, the temperature can be relatively low, thereby achieving good stability of the extract, and then being able to obtain a higher extract yield. The extraction method is simple, environmentally friendly, and has a wider range of applications.
[0014] In order to better implement the present invention, further, the filtrate obtained in S3 is frozen, and the freezing time is 24-48 hours.
[0015] In order to better implement the present invention, further, the freeze-drying time in step S4 is 15-30 hours.
[0016] In order to better realize the present invention, further, the wax gourd leaf powder is 100g and the volume of the water is 400ml.
[0017] A wax gourd leaf extract composite corrosion inhibitor comprising the wax gourd leaf extract corrosion inhibitor according to claim 1 and iodide.
[0018] The invention discloses an application of wax gourd leaf extract as a corrosion inhibitor in inhibiting copper corrosion.
[0019] Copper has properties such as electrical conductivity, thermal conductivity, ductility and antibacterial properties and is widely used in various fields. However, copper will also suffer a certain degree of corrosion during long-term service. In order to remove the corrosion products on the copper surface, acid pickling solution is often used to clean the copper surface. During the pickling process, sulfuric acid solution can not only remove the corrosion products on the copper surface but also cause a great degree of damage to the copper substrate. Therefore, in order to protect the copper substrate, corrosion inhibitors are often added to the pickling solution. However, traditional corrosion inhibitors have many problems such as low corrosion inhibition performance, poor solubility, serious environmental pollution, complex preparation process and high cost.
[0020] Working principle: Winter melon, also known as white winter melon, white melon, and pillow melon, is a plant of the Cucurbitaceae family. It is widely distributed throughout the world, but it is more common in tropical and subtropical regions, mainly in the southwest and south. "Shennong's Herbal Classic", "Compendium of Materia Medica" and "Rihuazi Materia Medica" all describe the medicinal value of winter melon. However, winter melon leaves are crop waste, and making them into natural, environmentally friendly corrosion inhibitors realizes the reuse of resources.
[0021] The invention grinds wax gourd leaves into powder, mixes the wax gourd leaf powder and water evenly, and packs the powder into polytetrafluoroethylene beakers, and then puts the powder into an autoclave for high-pressure extraction to obtain an extraction extract. The extract contains 2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-4H-chromene-4-one, 7-hydroxy-3-[4-hydroxy-3-(3-methyl-2-butyl)phenyl]benzopyran-4-one, p-hydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid and pyridine-3-carboxylic acid. When the obtained extract is used in the corrosion inhibition process of metal copper, especially in a 0.5M sulfuric acid medium, heteroatoms (such as N, O, S) and electron-rich atoms or functional groups in the extract are combined with a metal substrate in a physical and chemical adsorption manner to form an adsorption film on the surface of the metal copper, which can effectively block the direct contact between the corrosive medium and the metal surface, thereby reducing the corrosion of the pickling solution to the metal substrate and achieving the purpose of protecting the metal copper.
[0022] The present invention also provides a composite iodide obtained by compounding a wax gourd leaf extract corrosion inhibitor with iodide. In a 5M sulfuric acid medium, iodine and the wax gourd leaf extract can be quickly adsorbed on the surface of copper. After compounding, iodine ions can enhance the inhibitory effect of the wax gourd leaf extract corrosion inhibitor on copper corrosion, thereby enhancing the corrosion inhibition effect.
[0023] The wax gourd leaf extract provided by the present invention as a corrosion inhibitor has the advantages of good solubility, abundant material resources, simple preparation route, high corrosion inhibition efficiency and environmental friendliness, and can meet the demand for large-scale application of corrosion inhibitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the present invention will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A flow chart for preparing the wax gourd leaf extract corrosion inhibitor provided by the present invention;
[0026] Figure 2 The Fourier transform infrared spectrum of the wax gourd leaf extract provided by the present invention;
[0027] Figure 3 Four main chemical molecular structural formulas of the wax gourd leaf extract provided by the present invention;
[0028] Figure 4 (a) Nyquist plot, (b) Bode plot and (c) potentiodynamic polarization curve (Tafel plot) of the copper electrode provided by the present invention immersed in 0.5M sulfuric acid medium containing wax gourd leaf extract of different concentrations.
[0029] Figure 5 The present invention provides (a) Nyquist plot, (b) Bode plot and (c) Tafel plot of a copper electrode immersed in a 0.5M sulfuric acid medium containing different concentrations of wax gourd leaf extract + 16mg / LKI;
[0030] Figure 6 An equivalent circuit diagram for fitting EIS data provided by the present invention;
[0031] Figure 7 The Langmuir and Temkin adsorption isotherms obtained by impedance data fitting provided by the present invention;
[0032] Figure 8 The present invention provides SEM morphology images of a copper sample containing KI, wax gourd leaf extract, and wax gourd leaf extract + KI after being immersed in a 0.5M sulfuric acid solution for 15 hours.
[0033] Fig. 9 The present invention provides AFM morphology images of a copper sample containing KI, wax gourd leaf extract and wax gourd leaf extract+KI after being immersed in a 0.5M sulfuric acid solution for 21 hours.
[0034] Fig.10 The present invention provides an XPS graph of a copper sample containing wax gourd leaf extract after being immersed in a 0.5M sulfuric acid solution for 10 hours. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described below in conjunction with the accompanying drawings of the present invention.
[0036] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. At the same time, in the description of the present invention, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.
[0037] Example
[0038] Preparation method of wax gourd leaf extract corrosion inhibitor:
[0039] The following steps are involved:
[0040] S1: Wash the wax gourd leaves with water and dry them naturally;
[0041] S2: Grinding the dried wax gourd leaves into wax gourd leaf powder;
[0042] S3: Weigh 100g wax gourd leaf powder and 400ml water in a beaker and stir them evenly, then divide the stirred liquid into polytetrafluoroethylene cups, and then place them in an autoclave, soak them at a pressure of 5Mpa for 1.5h for extraction, filter to obtain a filtrate after the extraction reaction, and freeze the obtained filtrate for 48h;
[0043] S4: placing the frozen filtrate into a freeze drying box for freeze drying for 24 hours to obtain the wax gourd leaf extract corrosion inhibitor.
[0044] The following is a detailed description of the technical effects of the present invention using a degradation experiment.
[0045] This embodiment carried out an electrochemical test experiment. During the experiment, pure copper was used as the working electrode. During the electrochemical test, the copper electrode was sealed with epoxy resin to expose only one working surface (1 cm 2 ) In the corrosive medium, the workstation model used for electrochemical testing was Chi760E, and the three-electrode system was used for testing, in which copper was the working electrode, platinum was the counter electrode, and saturated calomel electrode was the reference electrode. Before the electrochemical test, the copper electrode was polished with sandpaper of 400, 800, 1200, and 2000 meshes in sequence until the entire electrode surface was polished flat, and then the copper electrode was ultrasonically treated in pure water and anhydrous ethanol, and then dried in cold air.
[0046] First, an open circuit potential test was performed with a test time of 2400s to allow the copper surface to obtain a stable state. Then an electrochemical impedance spectroscopy test was performed with a test frequency range of 105Hz to 10-2Hz and an excitation signal of a sine wave of 0.01V. Finally, a potentiodynamic polarization curve test was performed with a test interval of Eocp±0.25V and a scan rate of 0.001V / s. The concentration gradient of wax gourd leaf extract was 40mg / L, 160mg / L, 280mg / L, and 400mg / L, and a 0.5M sulfuric acid solution was used as a blank control. Each experiment was tested three times to obtain better reproducibility. The corrosion inhibition efficiency calculation formula using electrochemical impedance spectroscopy and polarization curve tests is:
[0047]
[0048] Among them, icorr,0 represents the corrosion current density when there is no corrosion inhibitor, icorr represents the corrosion current density when there is a corrosion inhibitor, Rp,0 represents the polarization resistance when there is no corrosion inhibitor, and Rp represents the polarization resistance when there is a corrosion inhibitor.
[0049] The functional groups contained in the wax gourd leaf extract in this example were tested using Nicoleti S50 Fourier transform infrared spectroscopy, and the test range was 4000 cm -1 Up to 400cm -1 ; The copper block size for SEM test is 0.5cm×0.5cm×0.5cm, and the copper block size for AFM and XPS test is 1×0.1×0.1cm 3 Before measurement, the copper block was polished on 400-7000 mesh sandpaper until the surface was smooth, ultrasonically cleaned with ultrapure water and anhydrous ethanol, and dried with cold air. The dried copper samples were immersed in sulfuric acid solutions containing and without wax gourd leaf extract for 15 hours, and then the copper blocks were taken out, ultrasonically cleaned with ultrapure water and anhydrous ethanol, and dried in cold air. The morphology was observed by scanning electron microscopy (JEOL-JSM-7800F). The copper samples (1×0.1×0.1cm 3 ) were used for XPS and AFM tests.
[0050] See attached Figure 2 , attached Figure 2 This is the infrared spectrum of wax gourd leaf extract. 3274cm -1 The peak at 2919cm is mainly attributed to the stretching vibration of OH or NH; -1 The peak at 1595 cm is related to the stretching vibration of saturated CH; -1 The peak of the C-H bending vibration in –CH3 is at 1408cm -1 at 1044cm-1 There is a sharp absorption peak at 1000 cm, which may be related to C–N or C–O stretching vibration; -1 The following absorption peaks correspond to aromatic and aliphatic C–H groups. Based on the above analysis, we can conclude that wax gourd leaf extract contains many functional groups containing oxygen and nitrogen atoms (O–H, N–H, C=C, C=N, C–N, C–O), which can protect copper from corrosion in sulfuric acid through physical and chemical action.
[0051] See attached Figure 3 , attached Figure 3 The chemical structural formulas of the five main components of wax gourd leaf extract are presented.
[0052] See attached Figure 4 , attached Figure 4 (a), (b), and (c) are the Nyquist, Bode, and Tafel plots of copper immersed in 0.5M sulfuric acid solution with and without wax gourd leaf extract corrosion inhibitor, respectively. Figure 4 As shown in (a) and (b), when the concentration of wax gourd leaf extract is gradually increased, the radius of the capacitive reactance arc of the impedance spectrum also increases, and its impedance modulus and phase angle also increase with the increase of its concentration. This shows that the addition of wax gourd leaf extract increases the impedance value of ion and charge movement in the medium, and the corrosion inhibitor molecules are adsorbed on the copper surface, thereby inhibiting the corrosion of copper in sulfuric acid. As shown in Figure (c), the polarization curve of the wax gourd leaf extract, the corrosion current and corrosion potential both move in a more negative direction, indicating that the wax gourd leaf extract is added to the sulfuric acid medium as a green corrosion inhibitor, which reduces the speed of charge movement and thus reduces the corrosion rate. Therefore, it shows a good inhibitory effect on copper corrosion. Table 1 is the data fitted by the Tafel extrapolation method. The table shows that after the addition of wax gourd leaf extract, the corrosion current density is significantly reduced. As the concentration of the corrosion inhibitor increases, the corrosion current density continues to decrease, and the corrosion inhibition efficiency increases.
[0053] See attached Figure 5 , attached Figure 5 (a), (b), and (c) are the Nyquist, Bode, and Tafel diagrams of copper immersed in 0.5M sulfuric acid solutions containing and not containing wax gourd leaf extract + KI, respectively. When a small amount of wax gourd leaf extract was gradually added to the sulfuric acid solution containing iodide, the radius of the capacitance loop of its impedance increased significantly, showing a good corrosion inhibition effect. As shown in Figure (b), compared with the blank, after iodide and wax gourd leaf extract were compounded, the impedance modulus and phase angle values also increased significantly, which increased by nearly an order of magnitude. This also shows that the compound of iodide and wax gourd leaf extract has an excellent sustained-release effect. Figure 5As shown in (c), with the increase of the concentration of wax gourd leaf extract + KI, the corrosion potential and corrosion current both move in the negative direction accordingly. Table 2 is the data obtained by fitting the polarization experimental data using the Tafel extrapolation method. It can be seen from the table that the corrosion current decreases with the increase of the synergist concentration, while the corrosion inhibition efficiency gradually increases. This is because the iodine and wax gourd leaf extract added to the sulfuric acid medium are quickly adsorbed on the surface of copper, resulting in a decrease in the corrosion rate of copper and a significant decrease in the number of free-moving electrons and ions in the solution, resulting in a significant decrease in the current.
[0054] See attached Figure 6 In order to quantitatively analyze the EIS data, the attached Figure 6 The equivalent circuit diagram in the figure was fitted to the EIS data of wax gourd leaf extract and wax gourd leaf extract + KI, and the fitted data are listed in Tables 3 and 4. As shown in Table 3, as the concentration of wax gourd leaf extract gradually increases, the corrosion inhibition efficiency also increases; as can be seen from Table 4, when 16 mg / L KI is added to the sulfuric acid medium containing 400 mg / L wax gourd leaf extract, the charge transfer resistance Rct increases significantly, because the adsorption film of the corrosion inhibitor on the metal surface becomes more complete and dense, resulting in an increase in the corrosion inhibition efficiency.
[0055] See attached Figure 7 , attached Figure 7 The Langmuir and Temkin isotherm curves were obtained by fitting the Tafel data, which showed that the adsorption of wax gourd leaf extract on the copper surface was a monolayer adsorption, and that both physical and chemical adsorption existed.
[0056] See attached Figure 8 , attached Figure 8 SEM images of copper immersed in 0.5M sulfuric acid solution with and without wax gourd leaf extract and wax gourd leaf extract + KI are presented. Compared with the blank, the copper surface with wax gourd leaf extract is much smoother, while the copper surface is more uniform and smoother after adding KI in the presence of wax gourd leaf extract, and the scratches on the copper surface are clearly visible. This explains the results of the electrochemical test.
[0057] See attached Fig. 9 , attached Fig. 9 The 3D morphology of copper immersed in 0.5M sulfuric acid solution without, with, and with wax gourd leaf extract and wax gourd leaf extract + KI is presented. As can be seen from the figure, the average roughness of the copper surface in the absence of corrosion inhibitor is 78.568nm, while the roughness after adding wax gourd leaf extract is significantly reduced to 28.24nm, and the roughness in wax gourd leaf extract + KI is reduced to 16.157nm. This result is consistent with the electrochemical results, indicating that wax gourd leaf extract has an inhibitory effect on copper corrosion, and the addition of KI enhances the inhibitory effect.
[0058] See attached Fig.10 , attached Fig.10 These are the XPS graphs of copper sheets immersed in sulfuric acid solutions with and without wax gourd leaf extract for 10 hours at 298K. Fig.10 (a) shows the Cu2p immersed in sulfuric acid solution containing and not containing wax gourd leaf extract, and the peaks of Cu2p1 / 2 and Cu(0) / Cu(I) and the shock peak of copper divalent appear; Fig.10 (b) shows the spectrum of C1s detected on the copper surface immersed in sulfuric acid solution with and without wax gourd leaf extract. Three forms of peaks appeared in Cu-Bare, namely CC, COO and OC=O, and the detected components may come from accidental carbon pollution; while in the wax gourd leaf extract at home, in addition to the peaks appearing in Cu-Bare, there is also a peak of C=C. Fig.10 (c) shows the O1s spectra detected on the copper surface immersed in sulfuric acid solution with and without wax gourd leaf extract. The Cu-Bare contains a peak of CuO / Cu2O, and the copper surface with wax gourd leaf extract added contains peaks of C-OH and CuO / Cu2O. Fig.10 (d) shows the copper surface detected after adding wax gourd leaf extract, and two forms of peaks, NC, N=C and N-Cu, appear respectively. This indicates that the wax gourd leaf extract is adsorbed on the copper electrode surface and reduces the corrosion of copper.
[0059] Table 1 Tafel fitting data of copper electrode immersed in sulfuric acid medium with and without wax gourd leaf extract
[0060]
[0061] Table 2 Tafel fitting data of copper electrode immersed in sulfuric acid medium with and without wax gourd leaf extract + KI
[0062]
[0063] Table 3 Impedance fitting data of copper electrode immersed in sulfuric acid medium with and without wax gourd leaf extract
[0064]
[0065]
[0066] Table 4 Impedance fitting data of copper electrodes immersed in sulfuric acid solution containing and not containing wax gourd leaf extract + KI
[0067]
[0068] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A wax gourd leaf extract corrosion inhibitor, characterized in that: The wax gourd leaf extract corrosion inhibitor comprises the following components: 2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-4H-chromene-4-one, 7-hydroxy-3-[4-hydroxy-3-(3-methyl-2-butyl)phenyl]benzopyran-4-one, p-hydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid and pyridine-3-carboxylic acid.
2. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 1, characterized in that: The following steps are involved: S1: Wash the wax gourd leaves with water and dry them naturally; S2: Grinding the dried wax gourd leaves into wax gourd leaf powder; S3: Weigh a certain amount of wax gourd leaf powder and a certain amount of water and stir them evenly, then place the stirred liquid in an autoclave for extraction, and after extraction for a certain period of time, filter to obtain a filtrate, and freeze the obtained filtrate; S4: placing the frozen filtrate into a freeze drying box for freeze drying to obtain the wax gourd leaf extract corrosion inhibitor.
3. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 2, characterized in that: In step S3, the pressure in the autoclave is 4-6 MPa.
4. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 2, characterized in that: During the high-pressure leaching reaction in step S3, nitrogen needs to be flushed into the autoclave.
5. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 2, characterized in that: In the step S3, the extraction time in the autoclave is 1-3 hours.
6. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 2, characterized in that: The filtrate obtained in S3 is frozen, and the freezing time is 24-48 hours.
7. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 2, characterized in that: The freeze-drying time in step S4 is 15-30 hours.
8. The method for preparing the wax gourd leaf extract corrosion inhibitor according to claim 2, characterized in that: The wax gourd leaf powder is 100g, and the volume of the water is 400ml.
9. A wax gourd leaf extract composite corrosion inhibitor, characterized in that: The invention comprises the wax gourd leaf extract corrosion inhibitor as claimed in claim 1 and iodide.
10. Use of the wax gourd leaf extract corrosion inhibitor according to claim 1 in inhibiting copper corrosion.